THE PRINCIPAL’S STRATEGIES ON IMPROVING TEACHER QUALITY AT MTSS MANBAUL ULUM BONDOWOSO - Munawaroh, Siti; Ali Wafi (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2025)
In the context of Islamic education, teacher quality is a crucial indicator that determines both the success of the institution and the learning outcomes of students. This study aims to describe the strategies employed by the principal of MTsS Manbaul Ulum Bondowoso in improving teacher quality. This research adopts a descriptive qualitative approach. Data were collected using the simak libat cakap method, which involved attentive observation of the principal’s presentation of strategies, supported by recording, note-taking, and interviews with relevant stakeholders. The data analysis process was carried out systematically through the stages of transcription, reduction, classification, tabulation, validation, interpretation, and conclusion drawing. Transcription converted oral data into written form, followed by data reduction to filter relevant information in line with the research focus. Subsequently, the data were classified by type, tabulated using a coding system, and validated through clarification with the principal, vice principals for curriculum and student affairs, as well as teachers. The final stage involved interpretation and formulation of conclusions. The findings reveal that the principal implemented transformational leadership strategies, continuous professional development, systematic internal supervision, and the creation of a collaborative work culture. These strategies proved effective in enhancing teachers’ pedagogical competence, professionalism, and commitment to the institution’s vision and mission. The results underscore the importance of strengthening the principal’s leadership role as a key factor in fostering a sustainable culture of quality in Islamic educational settings.